Facile oxidation of flavanones to flavones using [hydroxy(tosyloxy)iodo]benzene in an ionic liquid - Muthukrishnan, Murugan; Patil, P. S.; More, Shivaji V.; Joshi, Ramesh A. (Mendeleev Communications, 2005)
A method for the oxidation of flavationes to flavones has been developed using [hydroxy(tosyloxy)iodo] benzene (HTIB) in the room-temperature ionic liquid 1,3-di-n-butylimidazolium bromide ([bbim]Br-+(-)).

Optimization and scale up of production of alkaline protease from Conidiobolus coronatus - Laxman, Ryali Seeta; Sonawane, A. P.; More, Shivaji V.; Rao, B. S.; Rele, M. V.; Jogdand, Vitthal V.; Deshpande, V. V.; Rao, M. B. (Process Biochemistry, 2005)
Alkaline protease secreted by Conidiobolus coronatus has been evaluated extensively in tanneries and finds application in pre-tanning operations in leather manufacture. It is important to produce the enzyme in inexpensive and optimized media on large scale for the process to be commercially viable. The present paper describes optimization of fermentation conditions in shake flasks and scale up of production to 100 L in fermentors. The production is complete in 2-3 days comparable to bacterial fermentations. The organism utilized several carbon sources such as starch, sucrose, lactose, glucose and fructose for production. Soyabean meal at an optimum concentration of 2-3% was found to be best inducer. Diammonium hydrogen phosphate, casamino acids and Hi-media peptone gave activities comparable to yeast extract. Preservation and stabilization studies showed that glycerol conferred considerable stabilization at room temperature while ammonium sulphate precipitated enzyme at 0.9 saturation was best with stability up to 2 years even at room temperature. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Alkaline Protease; Conidiobolus; Fermentation; Optimization; scale up

Pictet-Spengler cyclization in room temperature ionic liquid: a convenient access to tetrahydro beta-carbolines - Muthukrishnan, Murugan; More, Shivaji V.; Garud, Dinesh R.; Ramana, C. V.; Joshi, Rohini R.; Joshi, Ramesh A. (Journal of Heterocyclic Chemistry, 2006)
1,2,3,4-Tetrahydro-beta-carbolines have been synthesized in moderate to good yields in short reaction time using the ionic liquid [bbim] BF4 as reaction medium and promoter. There was no need for the use of an additional catalyst normally employed in Pictet-Spengler condensation.

Enzymatic degumming of silk with microbial proteases - More, Shivaji V.; Khandelwal, Harish B.; Joseph, M. A.; Laxman, Ryali Seeta (Journal of Natural Fibers, 2013)
Degumming of Chinese bivoltine silk with alkaline proteases from various microbial sources was investigated and compared with commercial enzymes. Among the proteases tested, two fungal and two actinomycete proteases were promising, which showed weight loss similar to conventional method (19.58% to 21.78%). Conidiobolus brefeldianus and BOA-2 proteases were best enzymes, which showed weight loss similar to conventional method with low enzyme concentrations and in shorter time. No significant differences were found in tensile strength or elongation at break by enzymatic degumming indicating that there was no damage to the fiber. Scanning electron micrographs showed the sericin deposits were removed and the fibers were separated.
Keywords: Alkaline Protease; bivoltine; degumming; microbial; Silk; weight loss